2016
DOI: 10.1890/15-0753.1
|View full text |Cite
|
Sign up to set email alerts
|

The role of competition – colonization tradeoffs and spatial heterogeneity in promoting trematode coexistence

Abstract: Competition - colonization tradeoffs occur in many systems, and theory predicts that they can strongly promote species coexistence. However, there is little empirical evidence that observed competition - colonization tradeoffs are strong enough to maintain diversity in natural systems. This is due in part to a mismatch between theoretical assumptions and biological reality in some systems. We tested whether a competition - colonization tradeoff explains how a diverse trematode guild coexists in California horn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 66 publications
3
20
0
Order By: Relevance
“…After experimental setup, we dissected the extra sentinel snails ( n = 129), and found non‐patent infections in 12.4% of snails (consistent with previous results; Mordecai et al. ). Therefore, after experimental initiation, we allowed ~1 month for non‐patent infections to become patent, collected all experimental snails on 18 August, and screened them as before on 21, 25, and 28 August, removing snails that shed.…”
Section: Methodssupporting
confidence: 87%
“…After experimental setup, we dissected the extra sentinel snails ( n = 129), and found non‐patent infections in 12.4% of snails (consistent with previous results; Mordecai et al. ). Therefore, after experimental initiation, we allowed ~1 month for non‐patent infections to become patent, collected all experimental snails on 18 August, and screened them as before on 21, 25, and 28 August, removing snails that shed.…”
Section: Methodssupporting
confidence: 87%
“…This pattern is in line with results obtained by Mordecai et al. () in a similar trematode guild where the incidence of infection is negatively correlated with position in the dominance hierarchy at levels sufficient to promote coexistence of subordinates.…”
Section: Discussionsupporting
confidence: 92%
“…By contrast, subordinate species might invest more in reproduction within the snail (as an adaptive response for those species with a greater chance of being killed by dominants) and have longer‐lived eggs (as an adaptive response to increase arrival and survival; Mordecai et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, biotic factors can strongly influence local species distributions (Jablonski, ), and some studies have shown macroecological signals of such species interactions (Gotelli, Graves, & Rahbek, ). Further research may integrate biotic factors including species interactions such as competition (Mordecai, Jaramillo, Ashford, Hechinger, & Lafferty, ), specialization (Fjeldså & Lovett, ), population and community dynamics (Locey & Lennon, ; Ralston, DeLuca, Feldman, & King, ), distributional shifts (Knowles & Massatti, ) and niche differentiation (Brown et al, ). A key question is whether and how such factors contribute to the origins and maintenance of species endemism in some areas and not in others that share similar environmental characteristics.…”
Section: Discussionmentioning
confidence: 99%